Antifungal activity of onion (Allium cepa L.) essential oil on Candida albicans - Miftahur Rahmi; Felicia Aileen Agustia (Universitas Respati Yogyakarta, 2019)
Background:Onions (Allium cepa L.) contain essential oil that have sulfur compounds called thiosulfinates or isothiocyanates which are known to have antibacterial and antifungal effects. Minimum Inhibition Concentration (MIC) test is needed to determine the minimum concentration of onion essential oil which can inhibit or kill fungus test. Objectives: To determine the antifungal activity of essential oil in onion (Allium cepa L.) and to find out the Minimum Inhibitory Concentration (MIC) on Candida albicans. Methods:This research was an experimental study with disc diffusion method (Kirby Bauer) using Sabourond Dextrose Agar (SDA) media. Results: The results were obtained at concentrations of 20% (C1); 10% (C2); 5% (C3); 2.5% (C4); 1.25% (C5); 0.625% (C6); and 0.312% (C7) provided inhibition with an average diameter of 13.14 mm; 9.33 mm; 8.49 mm; 6.90 mm; 0 mm; 0 mm; and 0 mm respectively. Conclusion: Essential oil of onion (Allium cepa L.) could inhibit fungal growth of Candida albicans and Minimum Inhibitory Concentration (MIC) of essential oil onions (Allium cepa L.) indicated on concentration of 2.5% with a flat diameter average of 6.90 mm.